Remembering the master In memory of master José León Barandiaran - de Trazegnies Granda, Fernando (2016)
There only are a few lawyers that are born humanists. One of them was the master Jose Leon Barandiarán, a true humanist, a studious of the men without specialty or compartment that limit him. Even the generic specialty of law was left close to a multifaceted personality as the Master has. In this article, the author will pay tribute, as the thirty anniversary of his death, to one of the most important jurists of Peruvian Law. A reference to the legal culture and the largest contributor to the development of national law: Jose León Barandarián.